Our unswerving loyalty : a documentary survey of relations between the Communist Party of Australia and Moscow, 1920-1940 - Lovell, David W., 1956-; Windle, Kevin, 1947- (ANU E Press, 2008)
"This book brings together 85 documents from the Russian State Archives of Social and Political History (RGASPI), selected and introduced by the editors from a collection of thousands of documents concerning the relations between the Communist International and the Communist Party of Australia"--Provided by publisher